Synthesis of biologically relevant molecules - Braasch-Turi, Margaret, author; Crans, Debbie C., advisor; McNally, Andy, committee member; Prieto, Amy, committee member; Prenni, Jessica, committee member (Colorado State University. Libraries, 2023)
Natural products total synthesis and bioorganic chemistry rely on organic synthesis to produce the compounds for biological study. Natural products and some biomolecules are naturally found in extremely low concentrations. Organic synthesis made it possible to acquire the amounts needed for biological studies. The research described herein discusses both areas. In the body of this document, the bioorganic work regarding lipoquinones, particularly ubiquinones and menaquinones, is described. Appendix IV described the natural products work. Chapter 1 provides a more detailed explanation as to the circumstances that led to two different areas of research. Chapter 2 serves as the introduction to the bioorganic research. In this chapter, a review of the literature surrounding ubiquinones, plastoquinones, and menaquinones is complied with their properties at the forefront. Lipoquinones are incredibly hydrophobic molecules, and such properties are often ignored or misinterpreted in the literature. The review compares reported similarities and differences among the lipoquinones with respect to their headgroups, isoprene sidechain length, conformations, and location of lipoquinones in membrane environments. The review also highlights the need for and encourages more experimental studies to validate the computational work in the field. Chapter 3 discusses the conformation and location of ubiquinone-2 in AOT reverse micelles. Previous work with menaquinone-2 determined the truncated lipoquinone derivative adopted a folded conformation in organic solvents and in AOT reverse micelles and suggest menaquinone-2 is located near the lipid-water interface. We hypothesized ubiquinone-2 would also adopt a folded conformation in the membrane and be located near the lipid-water interface, but closer to the bulk water than menaquinone-2. We used 1D and 2D NMR spectroscopic methods to explore the solvent and membrane conformations and membrane location of ubiquinone 2. The conformations and locations of ubiquinone-2 were compared to menaquinone-2, and the location of ubiquinone-2 was found to be slightly closer to the interface than menaquinone-2. Chapter 4 provides a review of the literature regarding the synthesis of naphthoquinone derivatives. There are five main synthetic approaches that have been used to synthesize naphthoquinone derivatives. The categories are (1) nucleophilic ring methods, (2) sidechain homologations and extensions, (3) metal-mediated and radical reactions, (4) electrophilic ring, and (5) pericyclic reactions. The advantages and disadvantages of each approach are discussed regarding selectivity, number of steps, yield, and overall safety. Some approaches are simpler to carry out for the non-expert and successfully yield product, although stereospecificity and yields of the reactions are less, whereas other routes are higher yielding. Chapter 5 discusses the exploratory synthesis of menaquinone derivatives. The established Friedel-Crafts approach has poor regioselectivity, poor stereoretention of the first isoprene unit in the sidechain, and universally low yields. Using the knowledge gained in Chapter 4, a pericyclic approach using Diels-Alder adducts was used to exert regiocontrol of sidechain and maintain the stereochemistry of the sidechain. A convergent route was designed to provide access to a diverse library of sidechains to include E and Z isomers of the first isoprene unit and varying degrees of saturation along the sidechain. Appendix IV discusses the progress towards the total synthesis of versiquinazoline A and versiquinazoline B, alkaloids with anti-cancer properties and a unique pyrazinoquinazolinedione (6-6-6) and imidazoindolone (5-5-6) scaffold. Through this synthesis, the non-proteinogenic amino acid, 1-amino-1-cyclopropycarboxylic acid, was prepared to be used in the synthesis of versiquinazoline B. The synthesis of the 5-5-6 ring system explored the use of many peptide coupling conditions to afford a sterically hindered amide bond. After frequent unsuccessful trials, steps toward the total synthesis of versiquinazoline A were taken using alanine instead of 1-amino-1-cyclopropylcarboxylic acid. After successful amide coupling, the reoxidation of the aromatic sing system was explored using 2,3-dichloro-5,6-dicyanoquinone. This project ended prematurely due to the advent of COVID-19 and the passing of my advisor, Dr. Robert M. Williams.
Keywords: menaquinone; total synthesis; lipoquinone; ubiquinone; natural products